Duchenne muscular dystrophy hiPSC–derived myoblast drug screen identifies compounds that ameliorate disease in mdx mice - Sun, Congshan (JCI Insight, 2020)
Duchenne muscular dystrophy (DMD) is the most common muscular dystrophy. In the present study, when human induced pluripotent stem cells (hiPSCs) were differentiated into myoblasts, the myoblasts derived from DMD patient hiPSCs (DMD hiPSC–derived myoblasts) exhibited an identifiable DMD-relevant phenotype: myogenic fusion deficiency. Based on this model, we developed a DMD hiPSC–derived myoblast screening platform employing a high-content imaging (BD Pathway 855) approach to generate parameters describing morphological as well as myogenic marker protein expression. Following treatment of the cells with 1524 compounds from the Johns Hopkins Clinical Compound Library, compounds that enhanced myogenic fusion of DMD hiPSC–derived myoblasts were identified. The final hits were ginsenoside Rd and fenofibrate. Transcriptional profiling revealed that ginsenoside Rd is functionally related to FLT3 signaling, while fenofibrate is linked to TGF-β signaling. Preclinical tests in mdx mice showed that treatment with these 2 hit compounds can significantly ameliorate some of the skeletal muscle phenotypes caused by dystrophin deficiency, supporting their therapeutic potential. Further study revealed that fenofibrate could inhibit mitochondrion-induced apoptosis in DMD hiPSC–derived cardiomyocytes. We have developed a platform based on DMD hiPSC–derived myoblasts for drug screening and identified 2 promising small molecules with in vivo efficacy.